Cell wall composition in Cryptococcus neoformans is media dependent and alters host response, inducing protective immunity - Upadhya, Rajendra; Lam, Woei C.; Hole, Camaron R.; Vasselli, Joseph G.; Lodge, Jennifer K. (Frontiers in Fungal Biology, 2023)
Introduction Cryptococcus neoformans is a basidiomycete fungus that can cause meningoencephalitis, especially in immunocompromised patients. Cryptococcus grows in many different media, although little attention has been paid to the role of growth conditions on the cryptococcal cell wall or on virulence. Objective The purpose of this study was to determine how different media influenced the amount of chitin and chitosan in the cell wall, which in turn impacted the cell wall architecture and host response. Methods Yeast extract, peptone, and dextrose (YPD) and yeast nitrogen base (YNB) are two commonly used media for growing Cryptococcus before use in in vitro or in vivo experiments. As a result, C. neoformans was grown in either YPD or YNB, which were either left unbuffered or buffered to pH 7 with MOPS. These cells were then labeled with cell wall-specific fluorescent probes to determine the amounts of various cell wall components. In addition, these cells were employed in animal virulence studies using the murine inhalation model of infection. Results We observed that the growth of wild-type C. neoformans KN99 significantly changes the pH of unbuffered media during growth. It raises the pH to 8.0 when grown in unbuffered YPD but lowers the pH to 2.0 when grown in unbuffered YNB (YNB-U). Importantly, the composition of the cell wall was substantially impacted by growth in different media. Cells grown in YNB-U exhibited a 90% reduction in chitosan, the deacetylated form of chitin, compared with cells grown in YPD. The decrease in pH and chitosan in the YNB-U-grown cells was associated with a significant increase in some pathogen-associated molecular patterns on the surface of cells compared with cells grown in YPD or YNB, pH 7. This altered cell wall architecture resulted in a significant reduction in virulence when tested using a murine model of infection. Furthermore, when heat-killed cells were used as the inoculum, KN99 cells grown in YNB-U caused an aberrant hyper-inflammatory response in the lungs, resulting in rapid animal death. In contrast, heat-killed KN99 cells grown in YNB, pH 7, caused little to no inflammatory response in the host lung, but, when used as a vaccine, they conferred a robust protective response against a subsequent challenge infection with the virulent KN99 cells. Conclusion These findings emphasize the importance of culture media and pH during growth in shaping the content and organization of the C. neoformans cell wall, as well as their impact on fungal virulence and the host response.